부천지역 초등학생의 식품알레르기 발생 실태 및 다른 알레르기질환과의 연관성 - 박재영; 박가영; 한영신; 신미용 (Allergy asthma & respiratory disease, 2013)
Purpose: This study was performed to evaluate the current status of food allergy (FA) and to analyze the relationship between allergy to individual foods and other allergic diseases in elementary school children. Methods: We performed a questionnaire survey for FA, asthma, allergic rhinitis, and atopic dermatitis using International Study of Asthma and Allergies in Childhood questionnaires. A total of 1,929 students in 3 elementary schools were enrolled. Results: A total of 324 students (16.8%) had ever suffered from FA symptoms more than once. Only 64 out of 324 students (19.8%) were diagnosed with FA by doctors. The presence of soy allergy was associated with the increased risk of bronchial asthma (adjusted odds ratio [aOR], 5.90; 95% confidence interval [CI], 1.87 to 18.59). The presence of egg (aOR, 1.91; 95% CI, 1.04 to 3.52) and wheat allergy (aOR, 5.45; 95% CI, 1.94 to 15.36) were associated with the increased prevalence of allergic rhinitis. The allergic symptoms to fruits/tomato was associated with the increased risk of allergic rhinoconjunctivitis symptoms (aOR, 2.98; 95% CI, 1.18 to 7.47). The allergic symptoms to egg (aOR, 2.29; 95% CI, 1.22 to 4.29), wheat (aOR, 4.91; 95% CI, 1.86 to 12.95), and shrimp/crab (aOR, 2.48; 95% CI, 1.37 to 4.49) were associated with the presence of atopic dermatitis. Conclusion: The prevalence of FA of elementary school students in Bucheon-city was 16.8%. A significant positive association between the suspected foods and the other allergic diseases was found. Soy allergy was significantly correlated to having bronchial asthma and fruits/tomato allergy correlated with allergic rhinoconjunctivitis. KCI Citation Count: 12